Comparative Seismic Analysis, Design, and Cost Estimation of a Residential Building - Pokhrel, Mahesh; Adhikari, Ujjwal; Dhakal, Suvechha; Dhakal, Aashish; Ghimire, Sachita; Shrestha, Anup (International Journal on Engineering Technology, 2023)
The updated National Building Code (NBC 105:2020) for professionally engineered buildings provides guidelines for analyzing and designing earthquake-resistant buildings. Though it has been three years since the update of the NBC, the Indian standard code, IS 1893:2016, still seems to be prevalent; however, it has not been updated after 2016. Therefore, comparing the seismic behavior of buildings analyzed and designed by these two prevailing methods in Nepal is essential. This study aims to compare the seismic parameters, design results, and the total cost of the buildings for NBC and IS for a three-story with a staircase-cover residential building. The response Spectrum Method was used to analyze and compare the response parameters like base shear, story drift, and story displacement. The seismic response parameters are more significant; however, the total cost is not significantly greater (i.e., only 5.5% approx.) for NBC, though the base shear was relatively higher than IS. Thus, this study helps understand the structural performance and emphasizes the use of NBC in all parts of Nepal.